Kabar dari Koloni: Pandangan dan Pemberitaan Surat Kabar Belanda tentang turisme di Hindia Belanda (1909-1940) - Achmad Sunjayadi (Jurnal Kajian Wilayah, 2014)
This paper discusses the views regarding tourism, especially the role of Vereeniging Toeristenverkeer (VTV)-Association of tourism- in the Netherlands Indies from the newspapers published in the Netherlands. The newspapers are Het Vaderland (HV), Nieuwe Rotterdamsche Courant (NRC), Algemeen Handelsblad (AH) during the period of 1909 to 1940. From the three newspapers, the articles about promotion of tourism in the Netherlands Indies, are found to be dominant. They provide also an overview of criticism and suggestion about tourism in the Netherlands Indies, which can be understood because the three newspapers were the liberal newspapers.Keywords: the views of the Netherlands newspapers, colonial tourism, the Dutch East Indies